Oral Anticoagulation: Update on Anticoagulation With Vitamin K Antagonists and Non–Vitamin K–Dependent Oral Anticoagulants - Altiok, Ertunc (Dtsch Arztebl Int, 2018)
BACKGROUND: Much new evidence on oral anticoagulation has come to light in recent years. Non-vitamin-K-dependent oral anticoagulants (NOAC) have been developed and have been introduced into clinical practice. In this review, we present the current state of the evidence on anticoagulation for various indications with vitamin K antagonists (VKA) and with NOAC. METHODS: This review is based on pertinent articles retrieved by a selective search in PubMed (search terms: anticoagulation, atrial fibrillation, prosthetic valve, thrombosis, pulmonary embolism) and on specialty society recommendations and relevant guidelines from the years 2000–2018. RESULTS: The main indications for oral anticoagulation are atrial fibrillation, venous thromboembolism, and status post heart valve replacement. In patients with atrial fibrillation and without valvular heart disease, anticoagulation is recommended for men with a CHA(2)DS(2)-VASc score = 1 and for women with a score = 2. NOAC for this indication are associated with a marginally lower rate of stroke than VKA (3.5% vs. 3.8%, number needed to treat [NNT] = 333) as well as a lower rate of major hemorrhage (5.1% vs. 6.2%, NNT = 91). NOAC are contraindicated for patients with mechanical heart valves. Anticoagulation with VKA can be predictably antagonized. Among the various types of NOAC, the anticoagulant effect of dabigatran can be safely antagonized with an antidote; no specific antidote is yet available for apixaban, rivaroxaban, or edoxaban. CONCLUSION: The evidence base for anticoagulation over a time frame of several years is inadequate at present, and direct comparative data for the different types of NOAC are not yet available.